Study Design and Outcomes of Korean Obstructive Lung Disease (KOLD) Cohort Study - Park, Tai Sun (The Korean Academy of Tuberculosis and Respiratory Diseases, 2014)
BACKGROUND: The Korean Obstructive Lung Disease (KOLD) Cohort Study is a prospective longitudinal study of patients with chronic obstructive pulmonary disease (COPD), asthma, or other unclassified obstructive lung diseases. It was designed to develop new classification models and biomarkers that predict clinically relevant outcomes for patients with obstructive lung diseases. METHODS: Patients over 18 years old who have chronic respiratory symptoms and airflow limitations or bronchial hyper-responsiveness were enrolled at 17 centers in South Korea. After a baseline visit, the subjects were followed up every 3 months for various assessments. RESULTS: From June 2005 to October 2013, a total of 477 subjects (433 [91%] males; 381 [80%] diagnosed with COPD) were enrolled. Analyses of the KOLD Cohort Study identified distinct phenotypes in patients with COPD, and predictors of therapeutic responses and exacerbations as well as the factors related to pulmonary hypertension in COPD. In addition, several genotypes were associated with radiological phenotypes and therapeutic responses among Korean COPD patients. CONCLUSION: The KOLD Cohort Study is one of the leading long-term prospective longitudinal studies investigating heterogeneity of the COPD and is expected to provide new insights for pathogenesis and the long-term progression of COPD.